All things harmless, useful, and ornamental : environmental transformation through species acclimatization, from colonial Australia to the world - Minard, Peter Maxwell (Flows, migrations, and exchanges., 2019)
"Species acclimatization -- the organized introduction of organisms to a new region -- is much maligned in the present day. However, colonization depended on moving people, plants and animals from place to place, and in centuries past, scientists, landowners and philanthropists formed acclimatization societies to study local species and conditions, form networks of supporters and exchange supposedly useful local and exotic organisms across the globe. Pete Minard tells the story of this movement, arguing that the colonies, not the imperial centers, led the movement for species acclimatization"--